PEMBUATAN PERJANJIAN DIHADAPAN NOTARIS YANG MINUTA AKTANYA TIDAK DIBACAKAN - Ivan Iqbal; Sumriyah (JOURNAL SAINS STUDENT RESEARCH, 2024)
Human are legal subjects who often carry out legal acts in their daily lives, so that human can give birth to legal consequenses from what tehay have done in their lives. Apart from that,because humans are social creatures, it is natural that in their lives they often come into direct contect. With the people around them,both directly and indirectly. As social creatures, humans cannot be separated from agreements/bonds between one another,whether it is a sale and purchase agreement,borrowing and borrowing goods or other transaction. Making an agreements which is then often made by a notary becomes a necessity for someone to carry out large transaction, whether it is buying and selling land, company sheres and the like. So this article will try to present a normative review regarding the existence of an agreement. An agreement made by a notary,but there are terms of the agreement which are not implemented in the agreement,so this paper tries to normatively examine the validity or legality of such an agreement.